Pengaruh Pembelajaran Berdiferensiasi dalam Seni Tari Terhadap Motivasi dan Keterlibatan Siswa di Sekolah Menengah Pertama - Martlina Pasaribu (Jurnal Didaktika Pendidikan Dasar, 2024)
This research aims to investigate the effect of differentiated learning methods involving the use of interactive multimedia on dance learning. The research was conducted on seventh grade students at SMP Negeri 4 Binjai, namely the experimental group who received differentiated learning with interactive multimedia and the control group who received conventional learning. The differentiated approach is designed to accommodate individual differences in students’ understanding and skills regarding the art of dance. The research results show that differentiated learning with interactive multimedia significantly increases understanding of dance concepts, active student participation, and creative application of skills. These findings support innovative approaches to dance learning that can increase learning effectiveness and stimulate students’ interest in the arts. The implications of the results of this research can contribute to the development of a dance curriculum that is more responsive to students’ needs and interests in the information technology era. The use of technology in dance learning not only enriches the visual experience but also encourages active student participation through its interactive aspects. Conclusion, implementing differentiated strategies helps teachers accommodate variations in student learning styles, resulting in learning that is more inclusive and responsive to individual needs. As well as the importance of integrating technology in the context of dance while emphasizing the benefits of a differentiated approach in the classroom.